Study on the ecology and distributional patterns of the epigeous Gasteromycetes in Parque de Natureza de Noudar (Alentejo, Portugal) - Louro, Rogério (2012)
The influence of several environmental and antropic parameters were evaluated on productivity, diversity and distribution patterns of the Gasteromycetes, in Parque de Natureza de Noudar (Alentejo, Portugal). The study area is dominate by holm oak stands with and without shrubs (montado) and areas of pastures and grasses. In a minor scale, there are some cork oak stands, shrub lands and stream margins vegetation. The experimental design consisted on a stratified sampling procedure, based in the total area and land use of each biotope and the maximum sampling effort. Therefore, 45 circular plots (250 m² each) were distributed randomly and proportionally among the six biotopes present in the study area. All the plots were sampled monthly, from November of 2006 to April of 2007. During this period all the carpophores were identified, collected to evaluate the species productivity (number of carpophores) and some specimens were preserved for the reference collection (Herbarium of the University of Évora - UEVH). After the environmental characterization of the study area (climate, vegetation and soil), all data was analyzed using a Principal components analysis (PCA) followed by a hierarchical grouping of "clusters", using as aggregation method the "complete linkage." The results suggest that the presence of this heterogenic group of fungi is partly conditioned by vegetation type and management practices. On the other hand, productivity and phenology are more likely to be influenced by climatic conditions, particularly precipitation. The holm oak biotopes present the highest biodiversity of this group of fungi, whereas areas dominated by shrubs reveal the highest productivity. Within the holm oak biotopes, the montado biotope registers the highest number of Gasteromycetes trophic groups (mycorrhizal, humicolous, lignicolous and coprophilous), whereas in the pastures and grasses and in the streams biotopes no presences were registered. Ten of the total species, namely Bovista delicata, B. dermoxantha, Crucibulum laeve, Cyathus olla, C. stercoreus, Geastrum elegans, Handkea excipuliformis, Ileodictyon gracile, Lycoperdon atropurpureum and Vascellum pratense, are reported for the first time to the province of Baixo Alentejo. The species potential distribution maps may constitute a valuable tool for identifying and preserve areas of special mycological interest on the Parque de Natureza de Noudar.